PELAKSANAAN KEWENANGAN KEPALA DESA TERHADAP PEMBANGUNAN INFRASTRUKTUR JALAN DESA DALAM PERSPEKTIF OTONOMI DESA DI DESA SUKA DAMAI KECAMATAN RUPAT UTARA KABUPATEN BENGKALIS - Ega Julianda Putri; Gusliana HB; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Law Number 6 of 2014 concerning Villages, in Article 26 paragraph (1) states, "TheVillage Head is in charge of administering Village Government, implementing VillageDevelopment, Village community development, and Village community empowerment". TheVillage Law gains the position of the Village as the "spearhead of development" that is morecomprehensive and tangible by taking into account the principle of diversity, prioritizing theprinciples of village recognition and subsidiarity. Then Government Regulation Number 72 of2005 Article 7 letter b also provides an overview of the implementation of village autonomy in abroad, real, responsible manner, in which it is stated that government affairs are under theauthority of the Regency/City whose arrangements are handed over to the village. The programthat is of concern to the Suka Damai Village Government is the improvement of village roads asthe main means of transportation for the community. Based on this, this study aims to find outhow the implementation of the village head's authority on the development of village roadinfrastructure in the perspective of village autonomy in Suka Damai Village, Rupat UtaraDistrict, Bengkalis Regency.This thesis is a sociological legal research, that is, this research looks at theeffectiveness of the law on villages in implementing the authority of the Village Head in SukaDamai Village, Rupat Utara District, Bengkalis Regency. This study uses primary data sourcesand secondary data sources, also uses data collection techniques in this study are interviews, andliterature review, and concluded in a qualitative way.Based on the research conducted, the results and conclusions are obtained that theVillage Government continues to make improvements by utilizing simple materials producedfrom nature, such as forest wood. The Suka Damai Village Government, assisted by thecommunity, did not hesitate to repair the main axis road that was passed by the villagecommunity in their daily activities. However for maximum improvement, the Suka Damaivillage government is still waiting for budgetary funds from the center. As for the obstacles inthe implementation of the village head's authority on the development of village roadinfrastructure, namely the factors of limited budgets, the high need for village infrastructuredevelopment, and the lack of good communication between the government and tha community.Keywords: Village Head – Infrastructure Development - Village Autonomy